Power and society in the GDR, 1961 - 1979 : the "normalisation of rule"? - Fulbrook, Mary 1951- Hrsg (Berghahn Books, 2009)
The concept of 'normalisation' and the GDR in comparative perspective / Mary Fulbrook -- 'Aggression in felt slippers' : normalisation and the ideological struggle in the context of détente and ostpolitik / Merrilyn Thomas -- Economic politics and company culture : the problem of routinisation / Jeannette Madarász -- Rural functionaries and the transmission of agricultural policy : the case of Bezirk Erfurt from the 1960s to the 1970s / George Last -- The 'societalisation' of the state : sport for the masses and popular music in the GDR / Dan Wilton -- Communication and compromise : the prerequisites for cultural participation / Esther von Richthofen -- Learning the rules : local activists and the Heimat / Jan Palmowski -- Practices of survival, ways of appropriating 'the rules' : reconsidering approaches to the history of the GDR / Alf Lüdtke -- The GDR, a normal country in the centre of Europe / Ina Merkel -- How do the 1929ers and the 1949ers differ? / Dorothee Wierling -- Producing the 'socialist personality'? Socialisation, education, and the emergence of new patterns of behaviour / Angela Brock -- 1977 : the GDR's most normal year? / Mark Allinson -- 'Normalisation' in the GDR in retrospect : East German perspectives on their own lives / Mary Fulbrook